The effectiveness of using collaborative writing Strategy for writing ability of senior high school students - Ulfiatul Latifah; Siti Maria Ulfa; Iin Rachmawati (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2020)
This research explored the effectiveness of using collaborative writing strategy for writing ability of the students and it used quasi experimental for the method. This study emplyed two groups namely experimental group and the control group. Both classes received different treatment. For the experimental group, the students were taught by using collaborative strategy while the control were not. The population were 10th grade students of MA Al-Ibrohimy. The data collection technique used the covariance analysis (ANCOVA). Results indicated that the collaborative writing approach appears to be more effective than traditional method in teaching literacy. However, both the study and control groups demonstrated a statistically significant difference in writing skills when tested in post-test words. The test data were analyzed using covariance analysis (ANCOVA). Results indicated that the collaborative writing approach appears to be more effective than traditional method in teaching literacy. However, both the study and control groups demonstrated a statistically significant difference in writing skills when tested in post-test words.